2022
DOI: 10.1002/lno.12035
|View full text |Cite
|
Sign up to set email alerts
|

Springtime phytoplankton responses to light and iron availability along the western Antarctic Peninsula

Abstract: Light and iron availability are intertwined in controlling Southern Ocean primary production because several photosynthetic proteins require iron. Changes in light and iron availability can also affect phytoplankton species composition, which impacts nutrient cycling, carbon drawdown, and food web structure. To investigate the interactive effects of light and iron on phytoplankton growth, photosynthesis, photoacclimation strategy, micronutrient stressinduced protein expression, and species composition, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
(131 reference statements)
0
2
0
1
Order By: Relevance
“…Fe limitation in the Southern Ocean is known to have a significant impact on phytoplankton physiology (Schallenberg et al 2020). However, Joy‐Warren et al (2022) found that Fe did not limit spring phytoplankton growth despite low concentrations in this region. In Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Fe limitation in the Southern Ocean is known to have a significant impact on phytoplankton physiology (Schallenberg et al 2020). However, Joy‐Warren et al (2022) found that Fe did not limit spring phytoplankton growth despite low concentrations in this region. In Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Protein was extracted from 0.2‐ and 3.0‐ μ m polycarbonate filters and 0.22‐ μ m Sterivex™ filters and digested into tryptic peptides using S‐trap columns, following Joy‐Warren et al 2022, as described in the Supporting Information with the following modification: 750 μ L of 2% sodium dodecyl sulfate (SDS) extraction buffer (0.1 M Tris/HCl pH 7.5, 5% glycerol, 5 mM EDTA, 2% SDS) was added to each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Phaeocystis antarctica readily acclimates to a wide range of irradiances by altering its photosynthetic capacity to increase photosynthesis and decrease oxidative stress that damages the photosynthetic apparatus and forms reactive oxygen species (ROS; Falkowski & Raven, 2007; Kropuenske et al, 2009; Mills et al, 2010; Moisan & Mitchell, 1999). Under lower irradiances, cell size is reduced and pigment content (e.g., chl a per cell) and antenna size are increased (Moisan & Mitchell, 1999; van Leeuwe & Stefels, 1998), while acclimation to higher irradiances results in reduction of the pigment antenna size and an increase in photoprotective pigments including β‐carotene and xanthophyll pigments (Joy‐Warren et al, 2022; Mills et al, 2010; Moisan & Mitchell, 1999; van Leeuwe et al, 2014). Another possible advantage P. antarctica has to combat oxidative stress is high cellular concentrations of the antioxidants dimethylsulfoniopropionate (DMSP) and acrylate (Kinsey et al, 2016; Sunda et al, 2002).…”
Section: Introductionmentioning
confidence: 99%